Urbane Kontexte der Kulturproduktion Räume der Kreativwirtschaft. - Klaus, Philipp (TH Zürich, NSL, 2008)
Im Beitrag werden mit der Analyse der Beschäftigungsentwicklung der Kreativwirtschaft und ihre Teilmärkte in den Zürcher Stadtquartieren verschiedene Feststellungen über die Wechselbeziehungen von Kulturproduktion und Stadtentwicklung untermauert. Dazu gehören die Verschiebungen mehrerer Branchen aus traditionell kreativen Quartieren in die ehemaligen Arbeiter- und Industriegebiete. Mit den Teilmärkten Architektur und Design lassen sich die Veränderungen in der ökonomischen Basis der Kulturwirtschaft im Stadtgefüge nachzeichnen.

A tremendous rise in the supply and demand for cultural products and services brought about an economic sector that now manifests in our lives through all sorts of media and gadgets. The production of culture is closely tied to a range of developments in the cities. Specific milieus and neighborhoods provide innovation and new trends for the cultural sector. The city of Zurich is a prime example of how these developments come about. Employment in the creative industries came to more than 8% of its total employment figures for 2005. With the increasing importance of creative industries, a shift of creative enterprises from the traditional districts of cultural production to the trendy neighborhoods can be observed. This is shown by employment statistics and interpreted by questioning the concepts of clusters and innovative milieus. The question of space is crucial for innovation in the culture and in the creative industries.
Urban context of culture production - spaces of the creative economy.
Keywords: Stadtentwicklungsplanung; Stadtquartier; Gewerbe; Dienstleistung; Wirtschaftszweig; Architektur; Design; Standort; Standortwahl; Kreativwirtschaft; Kreativität; Teilmarkt; Milieu; Szene; Sozialraum; Kulturwirtschaft; Stadtpolitik; Standortmarketing; Stadtentwicklungspolitik; Neue Medien; Selbstständiger; Freiberufler; Zwischennutzung; Räumliche Verteilung